ChemInform Abstract: Formation of a Carbonyl Group ortho to a Biaryl Structure or a 6H‐Dibenzopyran by a Palladium/Norbornene‐Catalyzed Ordered Reaction Sequence. Issue 1 (17th December 2015) - Della Ca', Nicola; Fontana, Marco; Xu, Di; Cremaschi, Mirko; Lucentini, Riccardo; Zhou, Zhi‐Ming; Catellani, Marta; Motti, Elena
Abstract: A series of biaryls is synthesized in the presence of a palladium/norbornene catalyst system.